Pathological Findings in the First Case of Caprine Paratuberculosis (Johne's Disease) in Elazi? - Karadaş, Erkan; Metin, Nursal; Yaman, Ihsan (My University, 2000)
Caprine paratuberculosis (Johne's disease) was diagnosed according to pathomorphological findings in a 5-year-old indigenous female hairy goat in Elazi?. Diagnosis was confirmed by demonstration of Mycobacterium avium subspecies paratuberculosis (M.a. paratuberculosis) in the intestinal smears and tissue sections stained with the Ziehl-Neelsen (ZN) method, and also detection of specific M.a. paratuberculosis DNA by the Polymerase Chain Reaction (PCR).
Elazi?'da Bir Keçide Gözlenen ilk Paratüberküloz Olgusunda Patolojik Bulgular
Keywords: Elazi?; Goat; Paratuberculosis; Pathomorphological Findings